Iterative Operator Splitting Method for Coupled Problems: Transport and Electric Fields - Geiser, Jürgen (Journal of Informatics and Mathematical Sciences, 2011)
In this article a new approach is considered for implementing operator splitting methods for transport problems, influenced by electric fields. Our motivation came to model PE-CVD (plasma-enhanced chemical vapor deposition) processes, means the flow of species to a gas-phase, which are influenced by an electric field. We consider a convection-diffusion equation and a Lorence force in the electrostatic case. The iterative splitting schemes is given as an embedded coupling method and we apply such a scheme as a fast solver. The decomposition analysis is discussed for the nonlinear case. Numerical experiments are given with respect to explicit Adam-Bashforth schemes. We discuss the convergence behavior in time and space for the iterative schemes.